Recommendations for the management of diabetic macular oedema with intravitreal dexamethasone implant: A national Delphi consensus study. Issue 5 (September 2022) - Kodjikian, Laurent; Baillif, Stephanie; Couturier, Aude; Creuzot-Garcher, Catherine; Delyfer, Marie-Noelle; Matonti, Frédéric; Weber, Michel
Purpose: The intravitreal dexamethasone implant (DEX-I) is an alternative to anti-VEGF for the first-line treatment of diabetic macular oedema (DME). However, several questions remain regarding its routine use and its place in certain situations not always specified in current recommendations. A national consensus approach was, therefore, initiated by French retinal experts. Methods: An iterative Delphi consensus approach was used. A steering committee (SC) of seven experts analysed data from the literature to formulate statements divided into five key areas of treatment. These statements were submitted to the independent and anonymous electronic vote of 87 French retina experts among whom 39 expressed their opinion and therefore constituted the voting panel. Results: After two rounds of voting, 22 and 7 of 38 statements received a strong consensus and a good consensus, respectively. The consensus level was higher for statements regarding first-line indications and safety of DEX-I compared to those regarding efficacy assessment, reprocessing time or pathophysiological biomarkers. The panellists recommended the preferential use of DEX-I for patients with limited availability for multiple injections, those who needed to undergo cataract surgery or who had a recent cardiovascular history, and as a therapeutic alternative to anti-VEGF in patients with a history of vitrectomy, retinal serous detachment, hyper-reflective points or dry exudates in optical coherence tomography (OCT). However, some statements proposed by SC experts were not validated. Conclusion: This study provides some key recommendations to clinicians treating diabetic macular oedema, which may be useful when using intravitreal dexamethasone implants in daily practice.